Penggunaan Audit Klinis Sebagai Cara Pembelajaran untuk Meningkatkan Perilaku Peserta Didik PPDS Onkologi Radiasi Periode September 2010 - Maret 2011 - Fielda Djuita; Harsono Mardiwiyoto; Ova Emilia; Soehartati Soehartati (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: Clinical Audit is one of the formative evaluations that conducted to maintain and increase behavior and performance of the Radiation Oncology students, as an effort to maintain radiotherapy services and grant the quality of education. The objective of this study is to evaluate the role of clinical audit in improving students’ behavior.Method: This was a quasi-experimental research time series. We have done audit to the medical record chart of the residences at Policlinic I, II, III and stay at semester 3, 4, 5 in FK UI/RSUPNCM between September 2010 and December 2011 (T0). Audit had done by the author and one of the lectures. After analyzing the audit report, the reports were sent to the students one by one through email followed by forwarding it to the lecturer involved in this research. Then we continue the audit by performing the second clinical audit (T1) from January until March 2011. We used the mean score from the two auditors. The score divided into 4 groups as follows: hospital clinical record, treatment prescription, simulation and planning also evaluation during treatment. After that the author compared the audit score before and after intervention with t-test.Results: There were 16 Oncology Radiation students with 163 cases (To) and 156 cases (T1) who worked at Policlinic I, II and III. Behavior mean score is 1.9229 (T0), standard deviation 0.0514 and mean score after first intervention is 1.9764, standard deviation 0.0479 with p= 0.006.Conclusion: The students’ behaviors and performance are changed significantly after intervention.